Perancangan UML sebagai Rekomendasi Proses Bisnis Berdasarkan BMC di Geoff Max Bandung - Rikky Rundupadang (Fakultas Ekonomi Universitas Garut, 2018)
Timeliness of the supply of raw materials to the company is very important to support an effective and efficient business process. However, the delay in supply has a negative impact on its business processes. This happened at Geoff Max Bandung where the supply of raw materials from suppliers to the company experienced delays which affected the production process so that customer demand could not be fulfilled. This is related to the block channels on the Business Model Canvas (BMC). This study aims to create BMC that is happening at Geoff Max, make recommendations for improving BMC, and design a unified modeling language (UML) for business process recommendations based on BMC on block channels such as use case diagrams, use case scenarios, activity diagrams, sequence diagrams, and class diagrams so that customer demand can be fulfilled and sales do not fluctuate. The research method used is qualitative. Primary data collection was carried out through interviews with three narusmber, namely product manager, operational manager, and financial analyst at Geoff Max Bandung. Furthermore, secondary data collection comes from articles, previous research, books, and related reference journals. The results showed that Geoff Max Bandung had filled nine BMC blocks. The results of the research evaluation show that there is a need for recommendations for improvement in the block of key activities, key resources, and channels. Researchers also created UML designs that refer to block channels such as product pre-order, product delivery, quality control of products, distribute products, check the products, and product marketing. In addition, UML consists of five actors, namely: Geoff Max Bandung product development team, producers, Geoff warehouse, distributors, and end customers.